Processo de desenvolvimento de misturas em pó com café solúvel - Vanini, Lucimara Salvat (2016)
The commercialization of espress coffee and popularization of cappuccinos led to an increase on the development of new products with coffee. During the process of new products development, it is important to consider the final quality characteristics or attributes expected by the consumers. In this sense, the Quality Function Deployment (QFD) is a method used to hear, translate and transmit the client’s voice into the industry. Another tool of fundamental importance for the development of new products, is the experimental design, once it enables that the developed formulations are in accordance to the specifications required to achieve optimal conditions of a process, or evaluate the effects that some factors have over some desired responses. The objective of this work was to establish a methodology of development of mixtures with coffee (cappuccinos) applying the method of quality function deployment and experimental design using triangular surface response method. In this work it was presented a model as a result of the QFD analysis. The quality house was presented with all the information necessary for the product development (client and product requirements). For the experimental design, independent variables were represented by the ingredients: cocoa powder, soluble coffee and whole instant milk. The dependent variables (answers) were obtained by the acceptance sensorial analysis: overall flavor, coffee flavor, overall taste, chocolate taste, creaminess, dissolution and overall impression. For the attributes of chocolate taste, dissolution, creaminess and overall impression, the optimal proportions suggested corresponded to formulation 1 of the experimental design. For the attributes of overall flavor, coffee flavor and overall taste, the optimal percentages were within the limits studied for the variables instant milk and soluble coffee, and in the inferior limit of variable cocoa powder. Preference analysis was applied with formulation 1, one formulation considering overall taste attribute and one commercial sample. Results indicated that the formulation developed by the experimental design was the most preferred among participants. These results indicate that the use of the tools proposed in this work are useful on the development of mixtures based on soluble coffee.